2019
DOI: 10.15282/jmes.13.2.2019.16.0413
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of physical and mechanical properties of glycerol - modified natural rubber/starch - filled carbon black composites using two level factorial design

Abstract: A statistical model was developed in this study to describe cure characteristic, rebound resilience and tensile strength of natural rubber/starch composites which was prepared by using a Haake internal mixer. Response surface methodology (RSM) based on central composite centered design (CCD) was employed to statistically evaluate and optimize the conditions for maximum cure characteristic, rebound resilience and tensile strength and study the significance and interaction of carbon black and glycerol on rebound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…40,41 Such a framework is used to assess appropriate responses, and evaluate the relative importance of several influencing factors even when complex interactions occur. 42,43…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 Such a framework is used to assess appropriate responses, and evaluate the relative importance of several influencing factors even when complex interactions occur. 42,43…”
Section: Introductionmentioning
confidence: 99%
“…40,41 Such a framework is used to assess appropriate responses, and evaluate the relative importance of several influencing factors even when complex interactions occur. 42,43 In general, both of the MDPE and PET polymers have excellent mechanical properties (such as hardness and wear resistance), are abundantly available in the surrounding environment, but PET is essentially cheaper than MDPE. Nevertheless, using the date-seed nanoparticles (DSN) as a reinforcement material for these polymers would have a clear advantage e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the optimum tensile properties were achieved at a carbon black loading of 50 phr and glycerol content of 7%. This new formulation between rubber starch-filled carbon black composites are potential material for natural rubber-based products with acceptable mechanical properties [19].…”
Section: Introductionmentioning
confidence: 98%
“…It also affected the cure characteristics and improved the mechanical properties of NR filled with WG [12]. A maximum tensile strength of 23 MPa and rebound resilience of 71% were achieved for CB and the glycerol loadings at 50 phr and 7 phr, respectively, for the glycerol-modified NR/starch-filled CB composites [14]. Calcium lignosulfonate was introduced into styrenebutadiene rubber (SBR) and acrylonitrile-butadiene rubber (NBR) at a consistent ratio of 30 phr.…”
Section: Introductionmentioning
confidence: 99%